2018
DOI: 10.1002/ccd.27486
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenting followed by open heart surgery in 323 patients: One‐year results and influencing factors

Abstract: CAS followed by OHS is a safe and effective treatment for patients with concomitant carotid and cardiac disease within 1-year follow up. The interval between CAS and OHS, congestive heart failure, and renal insufficiency could obviously influence the 1-year results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Shishehbor et al 12 demonstrated that staged CAS-OHS should be considered as a first-line strategy if the 3-to 4-week delay to OHS is clinically acceptable. Recently, Dong et al 28 analyzed the influencing factors on major cardiovascular events and showed that patients with an interval of more than 5 days between CAS and OHS had significantly higher rates of 1-year freedom from combined major stroke, MI, and death from any cause than those with an interval of 5 days or fewer between CAS and OHS (96.2% vs 85.6%; P ¼ .001). However, in our study, the median staging interval time between CAS and CABG was 43.51 days after CAS.…”
Section: Discussionmentioning
confidence: 99%
“…Shishehbor et al 12 demonstrated that staged CAS-OHS should be considered as a first-line strategy if the 3-to 4-week delay to OHS is clinically acceptable. Recently, Dong et al 28 analyzed the influencing factors on major cardiovascular events and showed that patients with an interval of more than 5 days between CAS and OHS had significantly higher rates of 1-year freedom from combined major stroke, MI, and death from any cause than those with an interval of 5 days or fewer between CAS and OHS (96.2% vs 85.6%; P ¼ .001). However, in our study, the median staging interval time between CAS and CABG was 43.51 days after CAS.…”
Section: Discussionmentioning
confidence: 99%
“…3 Dong et al, in a recent study of 323 consecutive CAS-CTS patients, reported that "interlude" duration (time between procedures) of <5 days was associated with the primary composite endpoint, which suggests that the option of longer interlude duration may be appropriate for medically high-risk patients. 12 The choice of eptifibatide as a second antiplatelet offers several key advantages over conventional DAPT protocols based on an aspirin/clopidogrel combination. Eptifibatide, along with GIIBIIIA agents abciximab and tirofiban, emerged in the early 2000s in several large, randomized trials for coronary intervention, though there is relative paucity of data for its use in CAS.…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed that simultaneous surgical treatment increases trauma and the prevalence of adverse outcomes during the perioperative period. 2,5,12,16…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7,9,11 The revascularisation in patients with high-grade carotid stenosis by stage or simultaneous with the CABG procedure is recommended to reduce the incidence of cerebrovascular events. 12,13 Giannopoulos et al presented a hybrid method as a satisfying alternative to simultaneous surgical revascularisation, especially in high-risk patients. 9 The CEA and CABG staged procedure decreased cerebrovascular events but increased the chance of myocardial events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation